KEMITRAAN NEGARA, INDUSTRI, DAN MASYARAKAT DALAM PELAYANAN IBADAH HAJI DI INDONESIA (Studi Kritis Terhadap Pelaksanaan Pelayanan Haji Dalam Konteks Demokrasi Pelayanan Publik di Indonesia) - M. Ladzi Safroni (DIA: Jurnal Administrasi Publik, 2016)
This study seen from near about social phenomenon reality of public service implementation related to pilgrim hajj in this country. By looking public service management discourses, included human resources implementer and politic and public discourses involved in it with critical perspectives. Its focus to in-depth study partnership concept or government relationship, people (consumer), and business institution. Also could see emerging reaction either from hajj industry and umroh. As well as user citizen. This study using theory of structuration Giddens and several public management theory, theory of country, theory of governance to see public administration phenomenon of hajj service. While method that used is qualitative method with critical perspective. Data taking done in Surabaya and di Saudi Arabia. Informant selection performed purposively represented government, hajj businessmen, KBIH, and hajj congregation in 2012.        The result of this research indicate that partnership model is imbalance among state, industry and market. The government role be more dominant compared two other parties. Industry did not active anymore. While people more vulnerable in its role and strategic position. Complexities of hajj service, as religion worship, become public service system which produced more oriented to power holder that is state than businessmen and people. This study also able to identify state dominance practices and contradictions as well as interest conflicts which involved public service management practices.Keywords : three pillars partnership, state role, public service, hajj pilgrim